Influence of soil physical and chemical in supporting sorghum productivity and development - Vallentia Nisrina Qurratuain Annida (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Sorghum has been known in Indonesia for a long time, but its development is not as good as rice and corn. This is because there are still few areas that utilize sorghum plants as food. Land evaluation is a process of assessing the potential of a land used as the basis for sector development in an area that is useful for reorganizing existing land use to assist in making land use planning decisions. This study lies in the integration of detailed soil physical and chemical characterization with land use change into practical, site-specific development directions for sorghum cultivation at the village scale. Previous studies focus mainly on general suitability classification, this research links soil directly to management recommendations and planning, providing a decision-support for promoting sorghum as an alternative food crop in marginal agricultural areas in Yogyakarta. Methods: This study was conducted in Sitimulyo Village, Bantul, from October to December 2023. Field surveys, soil sampling, laboratory analysis of physical and chemical properties, and water quality measurements were carried out to assess soil characteristics across various land uses. Findings: The results obtained show that in general the condition of land suitability in Sitimulyo Village has a level of moderately suitable (S2) to suitable (S1) with limiting factors of rainfall, slope, and Cation Exchange Capacity. Conclusion: Recommendations from this study are to make efforts to improve and sufficient level of management of limiting factors to improve the land suitability class. In addition, there is a need for more review and counselling on sorghum farming to improve the social and economic conditions of surrounding farmers. Novelty/Originality of this article: This study lies in the integration of detailed soil physical and chemical characterization with land use change into practical, site-specific development directions for sorghum cultivation at the village scale. Previous studies focus mainly on general suitability classification, this research links soil directly to management recommendations and planning, providing a decision-support for promoting sorghum as an alternative food crop in marginal agricultural areas in Yogyakarta.